2020
DOI: 10.3390/jimaging6120130
|View full text |Cite
|
Sign up to set email alerts
|

FACS-Based Graph Features for Real-Time Micro-Expression Recognition

Abstract: Several studies on micro-expression recognition have contributed mainly to accuracy improvement. However, the computational complexity receives lesser attention comparatively and therefore increases the cost of micro-expression recognition for real-time application. In addition, majority of the existing approaches required at least two frames (i.e., onset and apex frames) to compute features of every sample. This paper puts forward new facial graph features based on 68-point landmarks using Facial Action Codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…However, the general problem with graph-based micro-expression recognition is the lack of large-scale in-the-wild datasets. To date, the recognition accuracy peaks at 87.33% over the SAMM dataset with LOSOCV as reported in Buhari et al 18…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…However, the general problem with graph-based micro-expression recognition is the lack of large-scale in-the-wild datasets. To date, the recognition accuracy peaks at 87.33% over the SAMM dataset with LOSOCV as reported in Buhari et al 18…”
Section: Introductionmentioning
confidence: 58%
“…On the other hand, Table 4 lists the benchmark geometric-based methods [15][16][17][18][19] with the full-face graph and full-face graph + A-EMM, which are denoted as experiment I and experiment II, respectively. From these results, Buhari et al, 18 reported the highest accuracies of 76.67%, 75.04%, 81.41%, and 87.33% over the SMIC, CASMEII, CAS (ME) 2 , and SAMM datasets, respectively. In Buhari et al, 18 the full-face graph utilized 68 landmarks from the raw images (denoted as ℝ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations